Penerapan Chatbot sebagai Alat Pembelajaran untuk Pengembangan Pendidikan Karakter - Putri, Tiara Eka; Ramadhan, Gilang (CV. Cendekiawan Muda Sriwijaya, 2024)
SMK Negeri 4 Kota Bengkulu is a state vocational high school located on Enggano Street, Pasar Bengkulu, Sungai Serut District, Bengkulu City. Currently, the learning process at SMK Negeri 4 Kota Bengkulu still utilizes textbooks and modules as learning media. The limited learning media in the learning process has led to a lack of student motivation to learn. Therefore, developing a chatbot as a learning medium for character education materials can help students learn independently and interactively at SMKN 4 Kota Bengkulu. This system development uses the Cross-Industry Standard Process for Data Mining (CRISP-DM) method with a dataset of 912 data, then divided into 85% for training data and 15% for validation data. The architecture used is a feed forward neural network with 100 epochs, achieving an accuracy of 91% and a validation accuracy of 92%.